TINJAUAN HUKUM KEWENANGAN JAKSA DALAM PEMERIKSAAN TAMBAHAN MENURUT ASAS DOMINUS LITIS BERDASARKAN KUHAP - Alfajri Firmansyah (Jurnal Hukum Jurisdictie, 2020)
As a product of the law touted as the great work of the nation Indonesia, KUHAP introduces a functional differentiation framework, where The investigation is entirely handed over to the police, while the prosecutor's office serves only as a public prosecutor and the conduct of the management of judges. In kuhap itself adheres to the principle of functional differentiation, will It raises a question as to what is the position of Dominus litis in the KUHAP when combined with the integrared criminal justice system in it it contains the principle of functional differentiation. It means when we leave. From the understanding that Dominus litis is the controller of the case, then the extent to which stages of the examination process that can be viewed as dominis litis Jaksaan This question is a consequence, when the relationship between police with the prosecutor at the investigation stage is only limited to coordination Functional. KUHAP which adheres to the principles of specialization, differentiation and complement, not only distinguishing and dividing tasks and authorities, but also provides a barrier to accountability for the scope of the investigation's duties, investigation, prosecution and examination at an in-ordered court hearing. The consequences that arise from the principle of functional differentiation, illustrated from several the case that led to a free verdict from the Panel of Judges, due to witnesses / The defendant revoked BAP a quo. Revocation of bap witness/defendant, due to pressure or engineering of the case at the stage of investigation conducted by the police as an investigator. The above incident clearly harms the prosecution. general and the accused himself.